PERANCANGAN KEMASAN PENGIRIMAN PRODUK (STUDI KASUS LITTLE THING BY EYRA) - Armawan, Ammar Dzun Nurain; Putri, Sheila Andita; Sadika, Fajar (Telkom University, 2024)
Abstrac: Lately, new business opportunies have emerged that can be done byentrepreneurs from various background which is the home culinary businesses or morecommonly called household businesses and the seller can use E-commerce to help sell theirproduct. This home-based culinary business iniated a variety of products such as dailycatering, hampers, drinks, and so on. One example of a household-based brand is Li琀琀leThing by EYRA which o昀昀ers silky milk pudding and milk co昀昀ee products. Li琀琀le Thing byEYRA operates with household-based producon and sales with digital plavorms,especially social media WhatsApp and Instagram. Products sold by Li琀琀le Thing by EYRAare sent to consumers using delivery services such as online motorcycle taxis and paxel sothere is a lot of potenal of damage when the product is in the hands of the delivery serviceproviders, therefore it is necessary to do case studies to develop packaging and packingmethods used by Li琀琀le Thing by EYRA. So as to reduce potenal damage so that the ownercan avoid loss of pro昀椀t and consumer con昀椀dence Keywords: packaging, packing, delivery